Potensi Kerabang Telur dalam Pakan Ayam Ras Telur Telur - Sumiati Sumiati; Erwan Erwan; Dwi Kusuma Purnamasari; Syamsuhaidi Syamsuhaidi; Suhartini Suhartini (LPPM Universitas Mataram, 2021)
The aim of this research is to know potention of the egg shells mill in ration toweard eggs production and Quality of the layer chiken. This research was conducted in August 2020 at Apitaik West Lombok, laboratory of Animal nutrition Animal Husbandri Mataram Univercity and laboratory of BPTP East Nusa Tenggara. 75 of layer chiken devide into 5 treatment was PI (0% egg shells +50% yellow corn +16% rise bren and 36% KLKS consentrat), P1I (5% eggs shells +50% yellow corn +16% rise bren and 36% KLKS consentrat), P1II (7% eggs shells +50% yellow corn, 36% KLKS consentrat) +16% rise bren), 5 replicetes and each replicates use 5 layer chiken and all of treatment give iso protein and iso energy ration. The parameter in this reaserch was eggs production, feed comsumtion, feed convertion, eggs weight and eggs quality. The result of this research were analysis by varians analysis above completely randomized design (CRD). The result showed that eggs producktion, eggs weight, feed cosumtion and feed convertion non significant effect (P>0.05), but was significant effect (P<0.05) on weight and thick of eggs shell It was concluded that giving egg shells to a level of 7.5% in the feed had enough potential to increase egg production and quality of laying hens with relatively good feed efficiency.